World War I - Faust, Daniel R. (World history: need to know., 2024)
"World War I reshaped the world as we know it and laid the groundwork for the second world war. But how did the fighting start? And what brought about its end? Explore the war that redrew the world map with easy-to-understand content tied to the curriculum of upper-elementary and middle school students and text written at a 2nd to 3rd grade reading level. Dyslexia-friendly font and design make learning accessible, and a recap at the end promotes checking for understanding to aid comprehension. It's key world history curriculum made approachable for all"--